Records Committee review for rare bird sighting of Lesser Black-backed Gull at Saylorville Dam, 1986 - Dinsmore, Stephen J.et al (1986)
Records Committee review for a Lesser Black-backed Gull at Saylorville Dam in Polk County, IA on November 29, 1986. Includes a record review document with votes, a summary of review, and three documentation forms submitted to the committee. Epson - sheet feed